Influenza vaccination in acute coronary syndromes patients in Thailand: The cost-effectiveness analysis of the prevention for cardiovascular events and pneumonia - Apirak Sribhutorn (2018)
© 2018 Science Press. All rights reserved. Background: Influenza vaccination has been clinically shown to reduce adverse cardiovascular outcomes in acute coronary syndrome (ACS) patients, but the economic perspectives can provide important data to make informed decisions. This study aimed to perform the economic evaluation of lifelong annual influenza vaccination for cardiovascular events and well-established pneumonia prevention. Methods: Lifetime costs, life-expectancy, and quality-adjusted life years (QALYs) were estimated beyond one-year cycle length of a six-health states Markov model condition on whether a hospitalization for ACS, stroke, heart failure, pneumonia, no hospitalizations occurred, or death. The comparison of three age-groups of 40-year-old-and-above, 50-year-old-and-above, and 65-year-old-and-above scenario was performed. Incremental cost-effectiveness ratio (ICER) and net monetary benefit (NMB) were presented as a societal perspective in 2016. The model robustness was determined by one-way and probabilistic sensitivity analyses. Results: The influenza vaccination was cost-effective in all age-groups, by dominant ICERs (lower cost with higher effectiveness) which was completely lower than acceptable willingness-to-pay threshold of Thailand (160,000 THB (4,466.8 USD) per QALYs), with a great incremental value of NMB. Especially, the 50-year-old-and-above scenario was shown as the most benefit at 129,092 THB (3,603.9 USD) for each patient. Conclusions: The annually additional influenza vaccination to standard treatment in ACSs was cost-effective in all age-groups, which should be considered in clinical practice and health-policy making process.